2018
DOI: 10.1016/j.psychres.2018.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and altruistic behavior in antisocial violent offenders with psychopathic traits

Abstract: Deficiencies in empathic functioning are considered a core characteristic of violent behavior. Enhancing empathy in aggressive populations may thus represent a promising intervention target. Hence, the aims of the present work were two-fold: First, we wanted to thoroughly assess empathic competencies and second, we aimed to investigate effects of an empathy induction on experienced empathy levels and prosocial behavior in a sample of violent offenders relative to matched controls. Empathy was assessed using bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 64 publications
2
28
0
2
Order By: Relevance
“…Studies with offenders have reported inconsistent and mixed findings, with some studies not finding any relationship between alexithymia and psychopathy (Möller et al, 2014) whereas others identifying positive (Kroner and Forth, 1995; Louth et al, 1998; Mayer et al, 2018) or negative (Pham et al, 2010) correlations between the two constructs. These inconsistencies could be due to the heterogeneity in offender samples in these studies with regards to gender [male (Kroner and Forth, 1995; Pham et al, 2010; Möller et al, 2014; Mayer et al, 2018) vs. female (Louth et al, 1998)], type of crimes committed [violent (Kroner and Forth, 1995; Mayer et al, 2018) vs. non-violent, including drug-related crimes (Möller et al, 2014)], and comorbidity with psychiatric disorders (Pham et al, 2010). Studies examining the relationship between psychopathy and alexithymia among students consistently find positive correlations between the two constructs (Grieve and Mahar, 2010; Lander et al, 2012); however, these findings are not representative of the general population (Hanel and Vione, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies with offenders have reported inconsistent and mixed findings, with some studies not finding any relationship between alexithymia and psychopathy (Möller et al, 2014) whereas others identifying positive (Kroner and Forth, 1995; Louth et al, 1998; Mayer et al, 2018) or negative (Pham et al, 2010) correlations between the two constructs. These inconsistencies could be due to the heterogeneity in offender samples in these studies with regards to gender [male (Kroner and Forth, 1995; Pham et al, 2010; Möller et al, 2014; Mayer et al, 2018) vs. female (Louth et al, 1998)], type of crimes committed [violent (Kroner and Forth, 1995; Mayer et al, 2018) vs. non-violent, including drug-related crimes (Möller et al, 2014)], and comorbidity with psychiatric disorders (Pham et al, 2010). Studies examining the relationship between psychopathy and alexithymia among students consistently find positive correlations between the two constructs (Grieve and Mahar, 2010; Lander et al, 2012); however, these findings are not representative of the general population (Hanel and Vione, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the inconsistencies between studies could be due to differences in the way psychopathy was measured. Some studies have used interview-based measures such as the PCL-R or the PCL:SV (Kroner and Forth, 1995; Louth et al, 1998; Pham et al, 2010; Möller et al, 2014), while others have administered self-report measures of psychopathy (Grieve and Mahar, 2010; Lander et al, 2012; Mayer et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, another meta-analysis (Miller & Eisenberg, 1988) and other more recent studies (Björkqvist, Österman, & Kaukiainen, 2000) point to a negative association between empathy and aggressive behavior. In addition to correlational evidence, the induction of empathy by confronting participants with the suffering of others has been shown to motivate altruistic behavior (Batson, Duncan, Ackerman, Buckley, & Birch, 1981) or the transfer of monetary resources in economic interactions (Klimecki, Mayer, Jusyte, Scheeff, & Schönenberg, 2016; Mayer, Jusyte, Klimecki-Lenz, & Schönenberg, 2018). Interestingly, the more that participants experienced empathy, the more they helped others in need (Batson et al, 1981; Klimecki, Mayer, et al, 2016).…”
Section: The Role Of Empathy Compassion and Empathic Distress In Inmentioning
confidence: 99%
“…It is possible that the norm violations in our sample are related to deficits in spontaneous empathising abilities 39 . Research by Mayer et al 40 suggests that these abilities might be trainable, since violent offenders increased their monetary distributions in a dictator game after an empathy enhancement intervention. Future research should establish whether anti-social offenders would decrease their norm violations with a treatment programme that increases their empathic concerns.…”
Section: Discussionmentioning
confidence: 99%